Development of eco-friendly, self-cleaning, antibacterial membrane for the elimination of chromium (VI) from tannery wastewater - Arif Z.; Sethy N.K.; Mishra P.K.; Verma B. (My University, 2025)
Hydrophobic polyvinylidene fluoride membrane was reformed to the hydrophilic membrane by incorporating synthesized titanium dioxide nanoparticles using Cajanus cajan seed extract. Spectroscopic and microscopic techniques characterized the composite membrane. The X-ray diffraction confirms the anatase phase of titanium dioxide nanoparticles of crystalline size 15.89 nm. The effect of titanium dioxide concentration on the thermodynamical and rheological properties on the polyvinylidene fluoride casting solution was investigated by the triangle phase diagram and viscosity measurement. It was concluded that titanium dioxide introduction caused thermodynamic enhancement, but the impact of rheological hinderance was higher at high concentrations. The polyvinylidene fluoride/titanium dioxide membranes were used as a bi-functional membrane to evaluate the rejection of chromium (VI) from wastewater; then, they were applied as sunlight-active catalyst membrane to reduce the concentrated chromium (VI) to chromium (III) by reduction. It was concluded that at 0.02 wt% of titanium dioxide, the maximum rejection of 85.59% and a% reduction of 92% was achieved with enhanced flux. © 2020, Islamic Azad University (IAU).